Analyses of relevant issues of talent development, selection and success in swimming - Revesz, L. (Semmelweis University, University School of Ph.D Studies, Sport and Educational Sciences, 2008)
Selection and Talent Management We assumed (H1) that coaches identify talented competitors as athletes with excellent conditional skills, quick and successful movement learning abilities and with good psychological characteristics. This assumption was only partly verified, as coaches did highlight psychological characteristics, i.e. coping with the stress of competitions and trainings, performance motivation and successful movement learning abilities when defining a talented athlete, however, conditional skills were not included among the most important factors. The Pedagogical Approach to the Question We assumed (H2) that from the point of view of the athlete, the coach-athlete relationship is the most similar to the teacher-student relationship. This assumption was verified, as athletes are most likely to compare the coach to a teacher. An analysis of the age groups shows that this role is diminishing with older athletes and adults rather consider the coach as a friend. We assumed (H3) that the most important components of the complex work of coaches are: knowledge of the profession, individual treatment of the athletes and motivation. We uphold this assumption as knowledge of the profession, individual treatment of the athletes and motivation all appeared as the most important factors characterising the work of a coach. Knowledge of the profession is a precondition of successful work, without which the work of the coach cannot be successful. This is supplemented by the individual treatment of the athletes, which is also important during the preparations. Success in Swimming We assumed (H4), that the factors that set successful athletes most apart from not successful athletes are anthropometric characteristics (height, weight) and the body surfaces necessary for propulsion. We can only accept this assumption in part, as we have found no significant difference between successful and non successful athletes in the case of anthropometric characteristics, and even in the case of body surfaces necessary for propulsion we have only found a significant difference with regards to the width of the hand and the length of the arm. We assumed (H5) that athletes successful in general psychomotor tests give better performance than those not successful. This assumption must be abandoned as there is no statistically highlightable difference between successful and non successful athletes in the case of general psychomotor tests. This result also goes on to verify the specific nature of swimming, the general psychomotor tests do not suffice for setting forth the criteria, for defining the necessary skills. We assumed (H6) that in the special discipline tests successful athletes give better performance than their not successful peers. We uphold this assumption as successful athletes have achieved better results during the special discipline tests than the non successful ones, therefore, using these results it becomes possible to define certain criteria of selection and preparation, since the results of the measurements show what results the athlete must achieve at each test. We assumed (H7) that in the discipline-specific psychomotor tests successful athletes give better performance than their not successful peers. We uphold this assumption as successful athletes have achieved better results during the discipline-specific psychomotor tests than the non successful ones. These tests can be applied with better results in the selection procedure, as the criteria of success are easy to define. Psychological Characteristics of Swimmers We assumed (H8), that successful athletes have significantly better results regarding the psychological factors measurable with the ACSI-28 test. We can only accept this assumption in part, as successful athletes show results significantly better than those of non successful swimmers only in the case of sub-scale Peaking under pressure. This factor is a defining part of the achievement, on the basis of which we can say that those who are successful are more able to prepare themselves mentally for a competition and once there, to peak under pressure. We assumed (H9) that the motivational environment of swimming is characteristically a Taskoriented environment and the Task-oriented values of successful athletes are significantly higher. We can only accept the first half of this assumption. The motivational environment of swimmers is characterised by Task-orientation, however, successful athletes do not have a significantly higher amount. This substantially means that the environment (climate) is a supporter, it aids development and provides the athletes with a possibility to keep developing further. We assumed (H10), that it is characteristic of swimmers to have a higher level of intrinsic motivation and that the intrinsic motivational values of successful athletes are significantly better than those of not successful athletes. This assumption must be abandoned as swimmers have a higher extrinsic motivational value, and successful athletes do not have significantly higher inner motivational values.